(Invited) Visualization of Conductive Filament of ReRAM during Resistive Switching by in-situ TEM. (14th September 2015) - Takahashi, Yasuo; Kudo, Masaki; Arita, Masashi
Abstract : Performance of in-situ-transmission electron microscopy (TEM) applied to analysis of the resistive random access memory (ReRAM) is reported. Recent progress of ReRAMs makes it indispensable to understand the resistive switching mechanism in order to guarantee the reliability of ReRAMs. Since the TEM provides a high resolution images of the nanostructure, in-situ TEM should be a powerful tool for the analysis if electrical characteristics of ReRAMs can be measured in the TEM. The two sample fabrication methods are applied to two different ReRAM devices. Switching characteristics, which are almost the same as those measured at the outside of TEM by the use of conventional ReRAM cells, are achieved together with clear images of formation and rupture of conductive filaments corresponding to the low and high resistance states. In addition, retention characteristics longer than 10 6 s, and SET/RESET pulse operation more than 100k times are confirmed during TEM observation. These results indicate that the in-situ TEM will be a powerful tool to analyze the reliability of ReRAMs.